Statistical analysis of rainfall data at iranamadu reservoir catchment in kilinochchi, sri lanka. - Jeerasinghe, D.A.M.; Sampath, D.S.; Suthakaran, N.; Pathirana, K.P.P. (University of Jaffna, 2018)
Iranamadu reservoir is the largest reservoir in Northern Province of Sri Lanka, which is located in Kilinochchi. Iranamadu tank is one of the ancient reservoir in Sri Lanka, which was built in 5th century. Capacity of the reservoir is 132 MCM and the catchment area of the reservoir is 588 km2. The reservoir was enlarged during the British era, and bund was raised up three times. Objective of the study was to analyze rainfall data and check whether data is statically suitable for further hydrological modeling. Numbers of rain gauge stations, which are available at Kanagarayan Aru river basin, were selected for the study including Iranamadu, Vavuniya, Vavunikulam, Mankulam, and Muthiyankaddu. Missing rainfall data is estimated using simple arithmetic mean and normal ratio method. Daily rainfall data from 2010 – 2016 was statically check for screening and consistency. Outlier test and Spearman’s rank correlation test also carried out for the data set. Results of the study are revealed that rainfall data are statistically distributed and suitable for further hydrological analysis.
Keywords: Consistency check; Iranamadu reservoir; Screening check; Spearman’s rank correlation test; Outlier test